The autophagic response to polystyrene nanoparticles is mediated by transcription factor EB and depends on surface charge - Song, Wensi (J Nanobiotechnology, 2015)
BACKGROUND: A number of engineered nanoparticles induce autophagy, the main catabolic pathway that regulates bulk degradation of cytoplasmic material by the lysosomes. Depending on the specific physico-chemical properties of the nanomaterial, however, nanoparticle-induced autophagy may have different effects on cell physiology, ranging from enhanced autophagic degradation to blockage of autophagic flux. To investigate the molecular mechanisms underlying the impact of nanoparticle charge on the nature of the autophagic response, we tested polystyrene nanoparticles (50 nm) with neutral, anionic, and cationic surface charges. RESULTS: We found all polystyrene nanoparticles investigated in this study to activate autophagy. We showed that internalization of polystyrene nanoparticles results in activation of the transcription factor EB, a master regulator of autophagy and lysosome biogenesis. Autophagic clearance, however, was observed to depend specifically on the charge of the nanoparticles. Particularly, we found that the autophagic response to polystyrene nanoparticles presenting a neutral or anionic surface involves enhanced clearance of autophagic cargo. Cell exposure to polystyrene nanoparticles presenting a cationic surface, on the other hand, results in transcriptional upregulation of the pathway, but also causes lysosomal dysfunction, ultimately resulting in blockage of autophagic flux. CONCLUSIONS: This study furthers our understanding of the molecular mechanisms that regulate the autophagic response to nanoparticles, thus contributing essential design criteria for engineering benign nanomaterials. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (doi:10.1186/s12951-015-0149-6) contains supplementary material, which is available to authorized users.